Strange hadron production in pp and pPb collisions at √sNN=5.02 TeV; Physical Review C; Vol. 101, iss. 6 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen